Foreign aid and the domestic politics of European budget support - Jörg Faust; Svea Koch (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
We analyse domestic factors within European donor countries that have influenced their provision of budget support. Budget support has been one of the most promising, and at the same time, controversial aid instruments aimed at improving aid effectiveness as well as donor harmonisation. Based on theoretical considerations, our econometric analysis for the 2002–2012 period shows that government ideology, the economic context in donor countries, as well as the structure of their aid systems have been important determinants of budget support provision. A comparison of Germany and the United Kingdom sustains these findings with qualitative evidence. Our findings also indicate that these ideological, economic and bureaucratic factors have worked as important barriers to improved donor harmonisation within Europe.
Keywords: 330; Deutsche + Europäische + multilaterale Entwicklungspolitik; Wirksamkeit und Evaluierung